2021
DOI: 10.1109/jbhi.2020.3009658
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Validation of Arterial Blood Pressure Using Photoplethysmogram Morphology Features in Conjunction With Pulse Arrival Time in Large Open Databases

Abstract: Although various predictors and methods for BP estimation have been proposed, differences in study designs have led to difficulties in determining the optimal method. This study presents analyses of BP estimation methods using 2.4 million cardiac cycles of two commonly used non-invasive biosignals, electrocardiogram (ECG) and photoplethysmogram (PPG), from 1376 surgical patients. Feature selection methods were used to determine the best subset of predictors from a total of 42 including PAT, heart rate (HR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 62 publications
0
16
1
Order By: Relevance
“…While some authors reported that they accounted for such a subject-dependent split (e.g., [ 6 , 8 , 10 , 12 , 20 ]) others did not and our results suggest that in this case a particularly high prediction performance might partly result from potential train/test split violations. However, it should also be noted that such a careful split is not always possible when using publicly available databases like the MIMIC-II subset where subject specific information is often not provided.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…While some authors reported that they accounted for such a subject-dependent split (e.g., [ 6 , 8 , 10 , 12 , 20 ]) others did not and our results suggest that in this case a particularly high prediction performance might partly result from potential train/test split violations. However, it should also be noted that such a careful split is not always possible when using publicly available databases like the MIMIC-II subset where subject specific information is often not provided.…”
Section: Discussioncontrasting
confidence: 74%
“…Yang et al constructed time series from morphological PPG features and PTT values. They divided the time series into high- and low-frequency components and fed them into a DNN and RNN for BP estimation [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The three methods mentioned will be explained in more detail in the following subsection. Still, it is relevant to mention that many studies consider PAT as a replacement for PTT [46,47,48,49,50,51,52], but these are not equal, but there is a relationship by the pre-ejection period (PEP) [29], which varies independently per person, hence the discrepancies in the literature about whether PTT is better than PAT or vice versa as an estimator of blood pressure, [53] because the results are still very varied in terms of accuracy [32,46,54,55,56,57].…”
Section: Adaptive Filtersmentioning
confidence: 99%
“…In recent years research mainly focused on BP estimation from cuff-less multi and single sensor solutions. The former often utilize time or phase differences between different signals (usually ECG and PPG or multiple PPG) related to the blood volume propagation through arteries [5,6,7,8,9]. The latter mainly exploit morphological properties of blood volume dynamics derived from PPG measurements on a particular site [10,11,12,13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%